Durian Peel Waste as An Alternative Material for Oxalic Acid Using The Nitric Acid Oxidation Method - Kurniati, Yuni; Cholilie, Irvan Adhin; Rahmadini, Anysah; Suwandevi, Nurul Hamida (Universitas Djuanda, 2024)
Durian (Durio zibethinus murr) was a tropical fruit from Southeast Asia. Based on the content, the durian peel waste has the potential to be used as a raw material in the process of making oxalic acid. The cellulose content found in durian peel is 50-60%, and there was lignin and starch content of 5% for each. Oxalic acid is an organic compound with the formula C2H2O4. This study aimed to determine the effect of nitric acid concentration and oxidation time of durian peel on yield, oxalic acid content, and the quality of the oxalic acid produced. The method used in this study was the oxidation process. The influential variables in the oxidation process with nitric acid were the concentration and heating time. The higher the nitric acid concentration, the greater the % yield of oxalic acid produced. The independent variables used were nitric acid concentration and time. This research used a factorial Completely Randomized Design (CRD) method with two factors, namely nitric acid concentration (HNO3) and reaction time, and nine treatment combinations were obtained. The concentrations used were 3 M, 4 M, and 5 M then the times used were 60, 70, and 80 minutes. The ratio between nitric acid and durian peel was 1:10 with a temperature of 75℃. The optimum yield occurred at a concentration of 4M HNO3 with a heating time of 80 minutes, where the yield obtained was 22.50%. Oxalic acid from a citric acid concentration of 5M and a reaction time of 80 minutes resulted in oxalic acid crystals melting at 98.6˚C. From the results of this analysis, the synthesized oxalic acid has the same characteristics as pure oxalic acid, so it can be concluded that the product produced from this research is oxalic acid and is classified as dihydrate oxalic acid.